2007
DOI: 10.1007/s11552-007-9048-0
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid Excision with Four-Corner Fusion: A Biomechanical Study

Abstract: Purpose Partial wrist arthrodesis is a commonly performed procedure for the treatment of posttraumatic wrist arthritis because of its ability to provide pain relief without sacrificing complete wrist motion. The purpose of this study was to evaluate the redistribution of force after fourcorner fusion and scaphoid excision, and to correlate the findings with the reported clinical outcomes. Methods Fifteen cadaveric wrists were used to study the biomechanics of the four-corner fusion. Pressure-sensitive film (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
5
15
0
2
Order By: Relevance
“…17 Arthritis can develop in the radiolunate joint secondary to the increased forces across the joint or to pre-existing or new cartilage damage. 4,5,8,18 Although the distal to proximal capitolunate fixation still creates a 1-mm guide wire hole in the lunate and the radius, it avoids the larger screw-head-sized holes that are created if the screw placement is performed in a proximal to distal direction.…”
Section: Discussionmentioning
confidence: 99%
“…17 Arthritis can develop in the radiolunate joint secondary to the increased forces across the joint or to pre-existing or new cartilage damage. 4,5,8,18 Although the distal to proximal capitolunate fixation still creates a 1-mm guide wire hole in the lunate and the radius, it avoids the larger screw-head-sized holes that are created if the screw placement is performed in a proximal to distal direction.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the lunate has been demonstrated biomechanically to be predictive of the total active motion of the wrist following midcarpal arthrodesis. 8,9,10 Intercarpal arthrodesis requires up to six weeks of wrist immobilisation in either a cast or a plastic splint before initiation of the rehabilitation period. Assessment of bone healing can be difficult, and only a CT-scan at this time can reveal the bone bridging trabeculae.…”
Section: Surgical Techniquementioning
confidence: 99%
“…A study of cadaveric wrists confirmed an increase in the mean total load in the lunate fossa after scaphoid excision and 4CF with no difference in the load across the triangular fibrocartilage complex (TFCC) area. 5 Theoretically, degenerative osteoarthritis could occur as a consequence of the 4CF or PRC due to the smaller articular contact area. In contrast, an SCL fusion model demonstrated an increase in scaphoid contact areas by 42% accompanied by a slight decrease in the lunate contact area (by 12%).…”
Section: Personal Outcomes and Literature Reviewmentioning
confidence: 99%
“…This leads to an increased load across the lunate fossa, as the scaphoid fossa is no longer articulating with the carpus. 5 Therefore, osteoarthritis is a risk, particularly in PRC. 6 The rates of osteoarthritis in 4CF were recently reported at 1% by a meta-analysis, 3 but only one of the eight studies included in the analysis had a greater than 5-year follow up.…”
mentioning
confidence: 99%